2019
DOI: 10.3389/fimmu.2019.02470
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Are Mediators of Fibrosis and Effector Cell Recruitment in Dermal Chronic Graft-vs.-Host Disease

Abstract: Allogeneic hematopoietic stem cell transplant (allo-HSCT) is often used to treat acute leukemia or defects of hematopoiesis. Its widespread use is hampered by graft-vs.-host disease (GVHD), which has high morbidity and mortality in both acute and chronic subtypes. Chronic GVHD (cGVHD) occurs most frequently in skin and often is characterized by pathogenic fibrosis. Mast cells (MCs) are known to be involved in the pathogenesis of other fibrotic diseases. In a murine model of cGVHD after allo-HSCT, C57BL/6J reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Skin fibrosis is a recognized complication of graft-versus-host disease (GVHD), and the fibrotic process associated with GVHD shares several key features with progressive SSc [ 117 ]. An increase in mast cells has been reported in the skin of human GVHD samples compared to normal skin [ 118 ], and mast cells are commonly found in areas with irregular collagen fibers and active fibroblasts along with other immune cells [ 119 ]. Murine models of GVHD also develop cutaneous fibrosis, which is accompanied by prominent mast cell degranulation [ 118 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ].…”
Section: Mast Cells In Cutaneous Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…Skin fibrosis is a recognized complication of graft-versus-host disease (GVHD), and the fibrotic process associated with GVHD shares several key features with progressive SSc [ 117 ]. An increase in mast cells has been reported in the skin of human GVHD samples compared to normal skin [ 118 ], and mast cells are commonly found in areas with irregular collagen fibers and active fibroblasts along with other immune cells [ 119 ]. Murine models of GVHD also develop cutaneous fibrosis, which is accompanied by prominent mast cell degranulation [ 118 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ].…”
Section: Mast Cells In Cutaneous Fibrosismentioning
confidence: 99%
“…An increase in mast cells has been reported in the skin of human GVHD samples compared to normal skin [ 118 ], and mast cells are commonly found in areas with irregular collagen fibers and active fibroblasts along with other immune cells [ 119 ]. Murine models of GVHD also develop cutaneous fibrosis, which is accompanied by prominent mast cell degranulation [ 118 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Studies have shown that GVHD mice treated with nedocromil sodium, a mast cell stabilizer, had less of a fibrotic response [ 126 ].…”
Section: Mast Cells In Cutaneous Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…We examined this further in our studies [ 38 ], finding that supernatants from activated mast cells did indeed induce fibroblast proliferation when compared to supernatants from quiescent mast cells. This lends credence to the idea of a mast cell/fibroblast feedback loop in cGVHD.…”
Section: Historical Perspective On Mast Cells In Fibrotic Chronic mentioning
confidence: 99%
“…Mast cells are present in connective tissues throughout the body and serve multiple functions including effecting or regulating allergic responses, innate and adaptive immunity, autoimmunity, and inflammation. Mast cells serve as mediators of fibrosis and effector cell recruitment through chemokine production in dermal chronic graft-versus-host disease following bone marrow transplantation (16). Li, Zhao, and colleagues (11) demonstrated that ischemia and oxidative stress in mice…”
Section: Allogeneic Mast Cells Senescence In Frcs and Dln Fibrosismentioning
confidence: 99%